The use of an open source fea solver on astandard engineering problem - Gajdoš, Tomáš; Tomek, Petr (My University, 2022)
The article deals with a FEAresults comparison of anopensource FEM softwareCODE_ASTER with acommercial software SolidWorks Simulation and Abaqus. The problem of astatically loaded spherical cap is solved. Result evaluation is aimed atloss of stability, i.e. limit load (equilibrium curve) when loss of stability occurs and its corresponding shapeof deformation. The response of thestructure is described by aload-deflection curve of atop of aspherical cap in axial direction.
Užítí open source FEA programu pro výpočet standardního inženýrského problému
Keywords: Abaqus; Code_Aster; FEA; FEM; Loss of stability; Salome_Meca; SolidWorks Simulation; Spherical cap; Abaqus; Code Aster; FEA; MKP; ztráta stability; Salome Meca; Solidworks Simulation; kulový vrchlík